Green-Synthesized Gold Nanoparticles from Centella asiatica for Colloidal Stability and UV Protection - Pistanty, Mingle A; Astirin, Okid Parama; Marliyana, Soerya Dewi; ., Solichatun (Journal of Cultural Analysis and Social Change, 2025)
Green synthesized gold nanoparticles (AuNPs) using Centella asiatica leaf extract and the influence of poly(vinyl alcohol) (PVA) as a respective secondary stabilizing agent were systematically studied. Formation of AuNP was verified by a color change and absorption peaks due to the surface plasmon resonance in the visible region. Several characterization techniques such as UV–Vis-spectrophotometry, particle size analysis and zeta potential measurement, scanning electron microscopy, Fourier transform infrared spectroscopy (FT-IR), and energy-dispersive X-ray (EDX) were employed. The PVA content dramatically affected the growth and dispersion of nanoparticles. The PVA-containing systems showed a larger hydrodynamic size and polydispersity, which implied competitive adsorption among phytochemicals and with PVA as well as polymer-bridging effects. In spite of the size increase, zeta potential and conductimetric measurements showed that colloidal stability was increasing as a result of steric stabilization. The FTIR and EDX studies confirmed a co-capping mode where the plant-based biomolecules remained attached on the AuNP surface along with adsorbed PVA. Functional testing using Sun Protection Factor (SPF) measurements showed the opposite trend; for all AuNP formulations without PVA, higher SPF values were measured that peaked at intermediate storage times. This observation indicates the existence of an optimal functional window where ordered aggregation improves UV scattering performance. Overall, the results underscore a non-monotonic relationship between colloidal stability and functionality in plant-mediated AuNP systems and the importance of tuning these parameters when designing sustainably nanoparticle-based materials.